Mineralocorticoid receptor antagonists in heart failure: a systematic review and meta-analysis - Zhang, Yue; Bao, Yin-Chao; Wang, Li-Xia; Zhao, Hong-Juan; Sun, Jing; Sun, Lin; Duan, Wei; Du, Ming; Wang, Lei-Jun; An, Qin-Yan; Yang, Wen-Ze (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMineralocorticoid receptor over-activation drives maladaptive myocardial fibrosis, vascular inflammation and renal sodium retention across the entire spectrum of left ventricular ejection fraction (LVEF). While steroidal MRAs have convincingly reduced hospitalizations and mortality in patients with heart failure and reduced EF (HFrEF), evidence remains fragmented for heart failure with mildly reduced (HFmrEF) or preserved EF (HFpEF), and no head-to-head data distinguish steroidal from non-steroidal agents. This study aimed to evaluate the effect of MRAs in patients with HF across the range of ejection fraction.MethodsSearched PubMed, Web of Science, Wanfang and Cochrane library (1 Jan 1987–10 Sep 2024) for randomized clinical trials (RCT) assessing MRAs (finerenone, spironolactone, eplerenone) in HFpEF, HFmrEF or HF. The primary endpoint was composite cardiovascular (CV) outcomes. Secondary endpoints included CV mortality, overall HF exacerbation events, safety, and adverse events. A meta-analysis was conducted using hazard ratios (HR), confidence intervals (CI), and relative risks (RR) to synthesize the findings.ResultsIn the analysis of nine RCTs, MRAs were associated with a 23% reduction in CV composite outcomes (RR: 0.77, 95% CI: 0.72–0.83, P < 0.00001), a 23% reduction in HF hospitalization risk (HR: 0.77, 95% CI: 0.70–0.84, P < 0.00001), and a 22% reduction in all-cause mortality (HR: 0.78, 95% CI: 0.72–0.85, P < 0.00001) in HFrEF patients, compared to a 17% reduction in CV composite events (HR: 0.85, 95% CI: 0.78–0.93, P = 0.0004), a 20% reduction in HF hospitalization risk (HR: 0.80, 95% CI: 0.73–0.89, P < 0.00001), and an 8% reduction in all-cause mortality (HR: 0.91, 95% CI: 0.85–0.99, P = 0.02) in HFmrEF/HFpEF patients. However, CV mortality was not significantly reduced in HFmrEF/HFpEF patients (HR: 0.92, 95% CI: 0.82–1.02, P = 0.13), but was reduced by 23% in HFrEF patients (HR: 0.77, 95% CI: 0.70–0.83, P < 0.00001). The incidence of any serious adverse events was similar between the MRA and placebo groups. The incidence of hyperkalemia was significantly higher in the MRA group (RR: 2.19, 95% CI: 1.97–2.43, P < 0.00001).ConclusionsMRAs should be considered for patients with HFrEF due to their substantial benefits. In HFmrEF or HFpEF, MRAs may confer benefit, though the effect is modest and hyperkalemia risk is higher, mandating close potassium monitoring.Systematic Review RegistrationPROSPERO CRD42022304966.